INPUT PRODUKSI TERHADAP PENDAPATAN USAHA PEMBESARAN IKAN NILA (Oreochromis niloticus) KOLAM AIR TENANG DI KOTA SUKABUMI (Suatu kasus Pembudidaya di Pokdakan Kota Sukabumi) - Yeni Yuliani; Euis Dasipah; Karyana KS; Dety Sukmawati; Tuti Gantini (Universitas Galuh, 2023)
ABSTRACTFish culture production factors are an important component of the fish culture production process that determines the income of fish farmers. This study aims to analyze the business of tilapia rearing in the city of Sukabumi, and the production factors that influence the income of the tilapia rearing business. This study is a quantitative study using primers collected through a survey using a questionnaire. The research data collection was carried out in January 2022 - February 2022. The analytical method used was Multiple Linear Regression. The independent variables used were land area, number of seeds, amount of feed and labor costs. While the dependent variable is income. Ordinal Least Square (OLS) method is used for hypothesis testing on Multiple Linear Regression. The results showed that simultaneously the income of tilapia rearing farmers was influenced by land area, number of seeds, amount of feed, and labor costs of 82.83%. However, partially, only the variables of Land Area, Number of Seeds, and Amount of Feed, which affect the income. Meanwhile, the labor cost variable has no significant effect on the income of tilapia cultivators. The elasticity value of the fish farming production input factor has an elasticity value of less than 1 which means it is inelastic. The total elasticity of production factors for land area, seeds, feed and labor is 1.008 or fish rearing business is classified as an increasing return to scale business, meaning that the proportion of increase in output is greater than the increase in production input. Thus, optimizing the use of production inputs is very important in the fish farming process in order to maximize the income of fish farmers.